2016
DOI: 10.2147/cia.s109560
|View full text |Cite
|
Sign up to set email alerts
|

Do empowered stroke patients perform better at self-management and functional recovery after a stroke? A randomized controlled trial

Abstract: BackgroundSelf-management after a stroke is a challenge because of multifaceted care needs and complex disabling consequences that cause further hindrance to patient participation. A 13-week stroke patient empowerment intervention (Health Empowerment Intervention for Stroke Self-management [HEISS]) was developed to enhance patients’ ability to participate in self-management.PurposeTo examine the effects of the empowerment intervention on stroke patients’ self-efficacy, self-management behavior, and functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 27 publications
1
102
1
2
Order By: Relevance
“…These include participation based therapy ( 290 294 ), quality of life centered care ( 240 , 295 310 , 345 ), community based rehabilitation ( 311 315 ), home based rehabilitation ( 132 , 193 , 316 335 ), self-management ( 336 , 337 ), family or care giver-led training ( 340 342 , 350 , 353 , 354 ), telerehabilitation ( 317 , 343 , 346 , 349 ), and early therapy/rehabilitation ( 174 , 338 , 339 , 347 , 348 , 351 , 352 , 355 , 356 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include participation based therapy ( 290 294 ), quality of life centered care ( 240 , 295 310 , 345 ), community based rehabilitation ( 311 315 ), home based rehabilitation ( 132 , 193 , 316 335 ), self-management ( 336 , 337 ), family or care giver-led training ( 340 342 , 350 , 353 , 354 ), telerehabilitation ( 317 , 343 , 346 , 349 ), and early therapy/rehabilitation ( 174 , 338 , 339 , 347 , 348 , 351 , 352 , 355 , 356 ).…”
Section: Resultsmentioning
confidence: 99%
“…Though rarely used in the context of stroke ( 384 ), application of self-management interventions for stroke rehabilitation has stimulated research interest in recent years ( 337 ), Despite the fact that stroke is an acute event, stroke survivors experience physical and psychosocial challenges in the recovery trajectory which renders stroke a chronic condition ( 385 ). Challenges faced include depression, functional and mobility disability, reduction in life roles, and a lack of social support ( 386 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bandura's cognition theory was commonly applied for stroke self-management program, and this kind of program contained meaningful and physical activities to further improve self-e cacy. [45][46][47] Similar to stroke self-management program, VR can provide task-oriented, imitative, and repetitive activities, and it also has the advantage to integrate these four principles. Additionally, according to theoretical concepts of Bandura's self-e cacy, the most feasible way to assist participants to obtain and improve self-e cacy is to use self-e cacy-related four principles.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these benefits are best transferred to daily life only when the program is personalized (mode of delivery, frequency, duration). In an empowerment intervention on stroke patients’ self-efficacy, Sit et al (2016) found that empowered patients reported better functional recovery, especially in activities of daily living, and better self-management of their cognitive symptoms than a control group receiving standard therapy.…”
Section: Patient Empowermentmentioning
confidence: 99%